Dampak Program Pemberdayaan Petani Terhadap Ketahanan Pangan Dan Ekonomi Masyarakat Desa Lookeu, Kabupaten Belu - Oktovianus Emanuel Bisik; Fransina W. Ballo; Maria Indriyani H. Tiwu (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study aims to examine the farmer empowerment program for food security and community economy. This study uses a qualitative descriptive approach to examine the problems studied. The sampling technique in this study uses purposive sampling . Data collection techniques are carried out by means of observation, interviews and documentation studies. Data analysis techniques in this study are carried out by reducing data, presenting data and drawing conclusions. The results of this study illustrate that the farmer empowerment program for food security in Lookeu Village has been carried out well by the village government. The farmer empowerment program is in the form of food availability, food availability stability and accessibility. In this case, the Lookeu Village government has distributed subsidized fertilizers, superior seeds, pesticides, assistance, farm roads, reservoirs and irrigation channels. Meanwhile, the farmer empowerment program for the community economy, which is reviewed from the community's income and the number of poor people, has increased family economic income through agricultural productivity. Thus, the farmer empowerment program effectively helps the community in maintaining food security and provides an increase in the community's economy which has an impact on reducing the number of poverty.